PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS KEARIFAN LOKAL TERINTEGRASI KARAKTER PELAJAR PANCASILA PADA MATERI BANGUN DATAR KELAS IV SEKOLAH DASAR - Zulfi Fatmawati; Nurhidayati; Rintis Rizkia Pangestika (LPPM Universitas Cipta Mandiri, 2024)
The independent curriculum is designed to improve the character of students in accordance with the Pancasila student profile. Mathematics learning is abstract, while elementary school age children are still in the concrete operational stage. This abstract nature can be realized through local wisdom. Interactive multimedia based on local wisdom integrated with Pancasila student characters is one of the developments of learning media which contains local wisdom from the Central Java region integrated with characters that suit the profile of Pancasila students. This research aims to 1) produce a product that is appropriate to the interactive multimedia development process based on local wisdom integrated with the character of Pancasila students. 2) determine the feasibility of interactive multimedia based on local wisdom integrated with Pancasila student characters in elementary school flat building materials. Interactive multimedia was developed using a 4-D model including four stages, namely define, design, develop, and disseminate. Results of research on the development of interactive multimedia based on local wisdom integrated with the character of Pancasila students: 1) This research produces a product in the form of interactive multimedia based on local wisdom integrated with the character of Pancasila students which can be used as teaching materials or learning resources in elementary schools. 2) the results of validation analysis by two expert lecturers and educators, media experts obtained a percentage of 92% in the very valid category, material experts obtained a percentage of 79% in the valid category, expert practitioners obtained a percentage of 99% in the very valid category. The results of the analysis of student responses obtained an average percentage of 90% in the very practical category. The results of the analysis of learning implementation obtained an average percentage of 98% with a very practical category. So the interactive multimedia developed can be used as an alternative teaching material or learning resource in elementary schools.